English Reading in Indonesian Islamic Boarding Schools: Needs and Materials - Fahriany Fahriany; Wahyunengsih Wahyunengsih (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
Pesantren, Islamic boarding schools in Indonesia, have a unique educational framework. Pesantren combines religious and general subjects, including English. However, existing English reading materials are still questionable in meeting the specific needs of pesantren students. This study explores the differing perceptions of English reading materials among students, teachers, and experts at four Islamic boarding schools (Pesantren) in Indonesia. The study used a quantitative research design involving 10th-grade students from four pesantren: Al-Kautsar Al-Akbar Islamic Boarding School (North Sumatra), Darunnajah Islamic Boarding School (Jakarta), Assaadah Pamulang Islamic Boarding School (South Tangerang), and An-Nahdlah Islamic Boarding School (Depok, West Java). Data collection methods included questionnaires for students, teachers, and experts. A one-way ANOVA found significant variations across five evaluation dimensions: content relevance, comprehension support, exercise quality, instructional clarity, and motivational appeal (F = 31.648, p < 0.05). Based on the data from the Bonferroni post hoc analysis, the most positive rating for English reading materials was shown by students, followed by teachers, and the lowest by experts. Each group has a unique and different perspective. The findings of this study indicate that current reading materials are sufficient to meet basic curriculum standards and student interests. Still, based on expert observations, they do not meet the standards for teaching quality. Teachers need to find a bridge between the realities of classroom practice and pedagogical objectives. Therefore, a collaborative approach is required to develop English reading skills that align with curriculum objectives, classroom implementation, and student involvement in Islamic Boarding Schools. Development of inclusive materials, collaboration on revision communication with the government, ongoing teacher training, and integration of student feedback are highly recommended for developing practical and relevant student reading materials in Islamic boarding schools in the context and culture of the Islamic boarding school itself.